2021
DOI: 10.1161/circulationaha.120.049844
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response as a Compensatory Mechanism and Potential Therapeutic Target in PLN R14del Cardiomyopathy

Abstract: Background: Phospholamban (PLN) is a critical regulator of calcium cycling and contractility in the heart. The loss of arginine at position 14 in PLN (R14del) is associated with dilated cardiomyopathy (DCM) with a high prevalence of ventricular arrhythmias. How the R14 deletion causes DCM is poorly understood and there are no disease-specific therapies. Methods: We used single-cell RNA sequencing to uncover PLN R14del disease-mechanisms in human induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Nonetheless, lack of CaT amplitude changes has been consistently reported under conditions of perturbed SERCA2a modulation by PLN, even if the latter was associated with significant mechanical derangement [18,19]. In particular, engineered heart tissue (EHT), also generated by our group from the same hiPSC-CMs used in the present study, was characterized by a marked decrease in force development in the face of normal CaT amplitude [20,21]. While the resilience of CaT amplitude to perturbations may be accounted for by a robust homeostatic control [22], deranged contraction in spite of unchanged Ca 2+ signal would require additional explanations, such as a decrease in myofilament response to Ca 2+ , a hindrance to cell shortening or, as suggested by findings in EHTs [20], energetic incompetence.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Nonetheless, lack of CaT amplitude changes has been consistently reported under conditions of perturbed SERCA2a modulation by PLN, even if the latter was associated with significant mechanical derangement [18,19]. In particular, engineered heart tissue (EHT), also generated by our group from the same hiPSC-CMs used in the present study, was characterized by a marked decrease in force development in the face of normal CaT amplitude [20,21]. While the resilience of CaT amplitude to perturbations may be accounted for by a robust homeostatic control [22], deranged contraction in spite of unchanged Ca 2+ signal would require additional explanations, such as a decrease in myofilament response to Ca 2+ , a hindrance to cell shortening or, as suggested by findings in EHTs [20], energetic incompetence.…”
Section: Discussionmentioning
confidence: 55%
“…Altogether, an alternative hypothesis for the pathogenesis of the clinical phenotype should be considered. An intriguing one is that the effect of PLN p.Arg14del on myocardial function may be independent of PLN role in modulating EC coupling, as recently suggested by the observation that PLN R14del phenotype may be reverted by enhancement of the "unfolded protein response" [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is yet unclear if protein aggregates are a cause or consequence of this disease, PLN aggregation clearly is a pathological biomarker as it preceded other cardiac abnormalities [ 15 ], and was resolved along with attenuation of HF. Along the same line of reasoning, Feyen et al recently demonstrated that knockdown of endoplasmic reticulum (ER) stress sensors exaggerated contractile dysfunction of PLN-R14del-induced pluripotent stem cell-derived cardiomyocytes, while stimulation of the unfolded protein response improved contractility and force development to amplitudes that were similar to cardiomyocytes derived from healthy donors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is similar to previous studies, whereby isogenic gene corrected iPSC lines were generated to study disease biology using patient-derived iPSC-CMs. [87][88][89][90] Further, the use of patient-derived iPSCs presumes that the genetic background is permissive for the disease without major limitations from disease-modifying effectors. 91 Finally, we employed snRNA-seq because conventional microfluidics-based single-cell RNA-sequencing technologies are not suitable for adult cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%